Vehicle Tracking System with Energy-efficient and Signal-efficient GPS Receiver - MINGCHAMPABANE, Khamsai; DIDTAPHONG, Xaysamone; PARNY, thay; KHONGSOMBOON, Khamphong (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This research aims to develop a vehicle tracking system using a GPS that is energy-efficient and has efficient satellite signal reception. The experiment compares the performance of different GPS modules under real-world environmental conditions. It also measures and evaluates how much energy the system consumes when using various microcontroller models. The research sets conditions to reduce the frequency of data transmission over the Internet network to achieve the most energy-efficient system. The experimental results show that the system can report position inaccuracies of no more than ±5m. The average speed of reporting new position data is 3.5 seconds, and energy savings of up to 15% are possible compared to the old system by modifying the code's execution sequence to reference the movement speed of the vehicle and setting conditions for data transmission over the Internet network.